CORRELATION COEFFICIENT BETWEEN EMPLOYMENT AND CONSUMPTION IN KOSOVO 2003 – 2009 - Shabani, Arburim; Gjinovci, Arsim; Asllani, Besim (European Scientific Journal, ESJ, 2012)
Challenges that faces the labor market in Kosovo and living standards of kosovars are the focus of researches of many kosovar and international institutions. High level of unemployment and household consumption which is mainly oriented in consumption of food were specific for Kosovo society.The aim of this paper is to analyse the labor market and living standard in Kosovo during the years 2003 - 2009. The goal of the survey is achieved by measuring the relationship between variables of the labor market and living standard.The data for analysis are used from annual and periodical reports of the Statistical Office of Kosova and publications from local and international research institutions.Initially, average levels are found for employment and unemployment in Kosovo during the years 2003 - 2009 by total employment, education and age. Also, the comparison has been made for the level of employment in Kosovo with some of the region countries and EU countries. The relationship between variables of employment and household consumption is measured by method of correlation coefficient.Findings show that household consumption in Kosovo is changing from year to year, being transformed from the dominance in food consumption, in the consumption of housing, clothing and transportation. Also urban households and households with higher education are increasing their budget for recreation, hotels,restaurants and health care.